Child labour in India - Mishra, Lakshmidhar (New Delhi, 2000)
This book-by a deeply committed civil servant who has travelled the length and breadth of India to address the problems of child labour-analyses the oppressive reality of Indian labouring children and provides perhaps the fullest macro-perspective on the nature and scale of the problem, as well as what this problem means in human and economic terms. Mishra critically examines constitutional and legal provisions on the subject, the national policy and programme of action, international instruments and recent international initiatives, and the role of NGOs, trade unions, central employers' organizations, and the media. He also examines the salutary role of public-interest litigation and the deleterious impact of protectionist moves by developed economies. In the concluding chapter the author brings these various themes together and examines how the problem can be addressed on a war footing.
Keywords: Labour and laboring classes - India